2016
DOI: 10.1021/acs.jproteome.6b00443
|View full text |Cite
|
Sign up to set email alerts
|

Missing Protein Landscape of Human Chromosomes 2 and 14: Progress and Current Status

Abstract: Within the C-HPP, the Swiss and French teams are responsible for the annotation of proteins from chromosomes 2 and 14, respectively. neXtProt currently reports 1231 entries on chromosome 2 and 624 entries on chromosome 14; of these, 134 and 93 entries are still not experimentally validated and are thus considered as "missing proteins" (PE2−4), respectively. Among these entries, some may never be validated by conventional MS/MS approaches because of incompatible biochemical features. Others have already been va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Based on RNA-Seq data from HPA, six MPs for which we obtained mass spectrometry evidence in sperm (FAM181A, DNAJC5G, LRRC9, ALLC, C2orf78, 17 MAP3K19) correspond to genes showing a medium expression level in testis (between 10 and 100 transcripts per million, TPM), seven others (ADAM20, TEX22, EVX2, SLC35F4, FER1L5, KIAA2012 and ANKRD30BL) correspond to genes with a low expression level (less than 10 TPM) and two others to genes for which the expression in testis was validated by quantitative RT-PCR while no RNA-Seq data was reported (HERVs) 14 .…”
Section: Targeted Ms Results Support Data Mining Prioritization Strategymentioning
confidence: 99%
“…Based on RNA-Seq data from HPA, six MPs for which we obtained mass spectrometry evidence in sperm (FAM181A, DNAJC5G, LRRC9, ALLC, C2orf78, 17 MAP3K19) correspond to genes showing a medium expression level in testis (between 10 and 100 transcripts per million, TPM), seven others (ADAM20, TEX22, EVX2, SLC35F4, FER1L5, KIAA2012 and ANKRD30BL) correspond to genes with a low expression level (less than 10 TPM) and two others to genes for which the expression in testis was validated by quantitative RT-PCR while no RNA-Seq data was reported (HERVs) 14 .…”
Section: Targeted Ms Results Support Data Mining Prioritization Strategymentioning
confidence: 99%
“…In this JPR issue, follow-up papers from each of those groups extend these findings with 206 additional missing proteins from sperm (Vandenbrouck et al, 42 PXD003947) and 47 additional missing proteins from testis (Wei et al, 43 iProx00076500) identified under the new guidelines. In addition, Duek et al 44 have presented an outstanding analysis of chromosomes 2 and 14 for missing proteins, theoretically detectable proteins, and proteins most promising for SRM analysis in sperm.…”
Section: Concluding Remarks and New Directionsmentioning
confidence: 99%
“…In particular for PE2 proteins, C-HPP investigators can approach to perform target proteomics in order to identify PE2 class MPs by utilizing genomics dataset (e.g., RNA-seq) obtained from some specific tissues or cell lines [30]. Duek et al, attempted to detect MPs from testis by analyzing RNA-seq data and proteomic profiling with MRM assays [38, 39]. …”
Section: Challenges For the C-hppmentioning
confidence: 99%